The determinants of self-reported health-related quality of life in a culturally and socially diverse South African community - Jelsma Jennifer; Ferguson Gillian (The World Health Organization, 2004)
OBJECTIVE: To determine factors predictive of the score on the visual analogue scale (VAS) of the EQ-5D questionnaire. METHODS: The responses of 1159 residents of a socially and ethnically diverse suburb of Cape Town, South Africa, to the EQ-5D questionnaire were analysed using forward stepwise multiple regression. The variables entered included ethnic group, religious affiliation (Christian or Muslim), income level, unemployment, recent illness or disability and each level of the five EQ-5D domains. FINDINGS: The model developed accounted for an adjusted r² of 0.234 and included 11 variables. In addition to the EQ-5D domains, the presence of a disability, an income of less than US$ 420 per month, unemployment and age in years were significant predictors of VAS score. CONCLUSION: The substantial contribution of health state to the VAS indicates that it is a valid measure of health-related quality of life (HRQoL) across population groups. However, the subjects with lower social status reported a worse HRQoL than their health state alone warranted and this variable might need to be taken into account if the VAS is to be used to compare health states across populations. This paper provides empirical evidence of how HRQoL is perceived by different socioeconomic, cultural, ethnic and religious communities within a developing country.